Heart failure management of the elderly patient: focus on frailty, sarcopaenia, cachexia, and dementia: conclusions - Coats, Andrew J Stewart (Eur Heart J Suppl, 2019)
With the ageing of populations heart failure is becoming more common and more complex. It is affecting ever older patients and the number of prevalent comorbidities is rising. Even as we continue to gain success in large-scale clinical trials with more effective therapies so our patients are becoming more complex. One of the biggest challenges is the effect of age. Frailty, comorbidity, sarcopaenia, cachexia, polypharmacy, and cognitive decline are all challenging our patients as never before and these challenges will be difficult for cash strapped health care systems to manage. For these reasons, the Heart Failure Association brought together a panel of experts to debate and review this complex area, championing the need for us to establish better ways of caring for the patients of the future.